Characterization of Poly(MAA-co-EDMA) Monolithic Column for High Performance Liquid Chromatography: Scanning Electron Microscopy, Thermodynamic Parameters and Linear Solvation Energy Relationship Methodology. (27th April 2018) - Shi, Jie-Hua; Zhao, Li-Hua; Shen, Guo-Feng
Abstract: A poly(Methacrylate-co-Ethyleneglycol dimethacrylate) monolithic column was prepared in situ for high performance liquid chromatography and characterized utilizing scanning electron microscopy, thermodynamic parameters and linear solvation energy relationship methodology. The results revealed that there were many microglobules forming the larger cluster in poly(Methacrylate-co-Ethyleneglycol dimethacrylate) monolith prepared under the selected preparation conditions, which composed continuously aligned macroporous channels through the monolith skeleton. The poly(Methacrylate-co-Ethyleneglycol dimethacrylate) monolithic column had a good permeability, a high mechanical stability. The interaction model for each probe molecule on the poly(Methacrylate-co-Ethyleneglycol dimethacrylate) monolithic column was invariable within the studied temperature range due to an excellent linear relationship between ln k and 1/ T for each probe molecule. The chromatographic retention for each probe molecule on the poly(Methacrylate-co-Ethyleneglycol dimethacrylate) monolithic column was an enthalpy-driven process due to |∆ H °| > | T ∆ S °| and ∆ G °<0. The main interaction forces of the poly(Methacrylate-co-Ethyleneglycol dimethacrylate) monolith with probe molecules contain hydrogen bonding interaction, hydrophobic interaction and dipole-dipole interaction. However, the contribution of each interaction was in the order of hydrogen bonding acidity > hydrophobic interactions > dipole-dipole interaction > hydrogen bonding basicity. In addition, the poly(Methacrylate-co-Ethyleneglycol dimethacrylate)monolithic column is suitable for the separation of both nonpolar and polar compounds.